Peranan Majelis Taklim Rahmtul Ummah dalam Meningkatkan Pemahaman Keagamaan di Kec. Jonggat Kab. Lombok Tengah - Ahmad Zaini Dahlan (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
This research aims to describe the role of the Rahmatul Ummah District Taklim Council. Jonggat, Central Lombok in increasing religious understanding. This research uses a qualitative approach because the data obtained is processed and explained in the author's description. In obtaining data, the author used observation, interviews and documentation methods. Data sources in this research include primary data sources, namely the results of interviews with caregivers, administrators and several congregation members of the District Taklim Council. Jonggat, Central Lombok, as well as secondary data sources originating from activity documentation. The findings from the role of the district taklim assembly. Jonggat, Central Lombok in increasing religious understanding, namely: 1. Building the congregation's faith, after attending the taklim assembly this Saturday morning the congregation felt an increase in their faith. 2. Fostering families in creating a sakinah family through routine Saturday morning recitation activities. 3. Empowering the poor by holding charity activities for orphans every month of Muharram. 4. Improved household economy with many congregations joining in reciting the Koran while selling. 5. As a place to learn religious knowledge, so that it can increase religious understanding. 6. Foster harmony among people with friendship.